Quizizz as a Medium on Students’ Vocabulary Mastery at SD Negeri 7 Payaraman, Ogan Komering Ilir - Sulistiani, Indah; Idris, Muhammad; Hermansyah, Hermansyah (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine whether or not there is an influence of quizizz media on vocabulary mastery in Indonesian class V elementary school subjects. This study used an experimental method with a research design in the form of a true experimental design. The researcher used a sample consisting of two classes, namely the experimental group in class VA with 20 students including 14 boys and 6 girls while the control group in class VB had 20 students which included 12 boys and 8 girls. In this study using data collection techniques in the form of tests and documentation. The research instrument was a multiple-choice test with 20 valid questions. Based on the results of the hypothesis test using the t-test of two independent samples (independent sample t-test) the value of t-count is 4.123 and t-table is 1.686 with α = 0.05 and df = 38, then t-count ˃ t-table so that Ha is accepted and Ho is rejected so that it can be it was concluded that there was an influence of quizizz media on vocabulary mastery in grade V Indonesian subjects.